The Epigenetic Modification of Epigallocatechin Gallate (EGCG) on Cancer - Yang, Linqi; Zhang, Wenqi; Chopra, Saiyam; Kaur, Deeepjyot; Wang, Huibing; Li, Meng; Chen, Pingping; Zhang, Wei (Current Drug Targets, 2020)
Among the major components of green tea, epigallocatechin-3-gallate (EGCG) is the most effective for its anti-cancer characteristics. The bulk of studies provide the mechanisms of suppressive function of EGCG are involved in alteration of cancer cell cycle, development, and apoptosis through activation/inhibition of several signal pathways. Another mechanism that explains the multiple effects exerted by EGCG in cancer is the epigenetic change by DNA methylation or methyltransferases, histone acetylation or deacetylases, and no coding RNAs (micoRNAs). Furthermore, decontrolled expression of miRNA transcription has been tested to be directly regulated by oncogenic and tumor-suppressor transcription factors. Recently, several proteins have been identified as miRNA direct interactors by EGCG. However, the mechanisms explaining the action of miRNA being modulated by EGCG have not been completely understood yet. This review summarizes the state of epigenetic change being modulated by EGCG in a variety of cancers and oncogenic and tumor-suppressor transcription factors.
Keywords: Epigallocatechin-gallate (EGCG)